Status of maternal serum B vitamins and pregnancy outcomes: New insights from in vitro fertilization and embryo transfer (IVF-ET) treatment - Zhang, Ling; Wu, Li-mei; Xu, Wei-hai; Tian, Yu-qing; Liu, Xu-ling; Xia, Chen-yun; Zhang, Lin; Li, Shi-shi; Jin, Zhen; Wu, Xiang-li; Shu, Jing (Frontiers in Nutrition, 2022)
The influence of B vitamins on human fertility and infertility treatments remains elusive. This study investigated the association of most B vitamins with IVF-ET outcomes. A total of 216 subjects aged <35 y were recruited from their first oocyte retrieval cycles. Blood samples were collected before oocyte pick-up, and serum levels of riboflavin, niacin, pantothenic acid, vitamin B6 (including PA and PLP), folate, and methylmalonic acid (MMA) were detected using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Endpoints were summarized into three groups according to tertiles (lower, middle, and upper) of each vitamin index, and the association of serum vitamin status with intermediate and clinical outcomes were analyzed using a generalized estimating equation model. Higher riboflavin levels were associated with elevated probabilities of top-quality embryos, as well as clinical pregnancy after embryo transfer. A greater likelihood of transferable embryos was found under the middle tertile of serum folate. Similarly, a negative correlation of serum MMA, a marker of vitamin B12 deficiency was identified with top-quality embryos. No significance was observed for other vitamins in terms of all endpoints. Therefore, sufficient levels of pre-conception riboflavin, folate, and vitamin B12 are recommended for successful infertility treatment and pregnancy planning; further evidence is needed to confirm our conclusion.